Biofuel-water-land nexus in the last agricultural frontier region of the Brazilian Cerrado. (1st December 2018) - Rodriguez, Renata del G.; Scanlon, Bridget R.; King, Carey W.; Scarpare, Fabio V.; Xavier, Alexandre C.; Pruski, Fernando F.
Highlights: Potential biofuel expansion was quantified in the agricultural frontier in Brazil. Soybean water footprint is 8–14 times higher than that of sugarcane in study area. Water availability limits potential for sugarcane expansion relative to soybeans. Irrigation increases biomass production relative to rainfed management by 2–4 times. Water-land trading through irrigation of bioenergy crops conserves native vegetation. Abstract: The sustainability of biofuels depends on considering the environmental consequences of using water and land resources for bioenergy production. The objective of this study was to assess the potential for biofuel crop expansion by combining water footprint, water availability, and land availability in the last agricultural frontier region of Brazil using the Corrente Basin as a case study. Results show that the water footprint (ratio of water consumption to biomass or energy production) of sugarcane is low (114–190 m 3 Mg −1 ) reflecting high water consumption (∼9000 m 3 ha −1 ) divided by high crop yield (∼50–80 Mg ha −1 ), including millable stalks. However, water consumption for sugarcane grown in this area (9370 m 3 ha −1 ) exceeds water availability in much of the basin (90th percentile of streamflow), which limits sugarcane expansion. In contrast, the water footprint of soybeans (900–2600 m 3 Mg −1 ) is 8–14 times higher than that of sugarcane, reflecting much lower water consumption (∼1500–3800 m 3 Mg −1 ) and even lower crop yield (0.7–4.3 Mg ha −1 ), limited to grains, relative to sugarcane. The low water consumption of soybeans allows expansion under rainfed agriculture during the wet 1st harvest season over 22% of the region and under irrigation during the dry 2nd harvest season over 13% of the region, without the need for deforestation of the Cerrado biome. This soybean expansion represents ∼20 × 10 6 GJ of energy supply per year, ∼4 times current production. Surface water availability for irrigation extends into the dry season because of substantial groundwater discharge to streams during the dry season. Irrigation increases biofuel crop yield of sugarcane and soybeans, reducing land area required to produce an equivalent amount of biomass by 2 to 4 times relative to rainfed management. Therefore, water can be traded for land by expanding irrigated biofuel production, conserving more native Cerrado vegetation. Considering water and land requirements relative to availability for bioenergy crops provides data on potential increases in bioenergy production while minimizing clearing of native vegetation in the Brazilian agricultural frontier.